Big river : resilience and renewal in the Columbia Basin - Pearkes, Eileen Delehanty, 1961- (Braided River, 2024)
"Illuminates the ecological, hydrological, geological, and cultural beauty and activity of the Columbia River watershed, featuring rich, comprehensive images of the land, river, and people, with a focus on the importance of the renegotiation of the river treaty"--